Rancang Bangun Sistem Pakar Diagnosa Penyakit Ayam Bangkok - Aprih Widayanto; Joko Dwi Mulyanto; Ade Sulistyono (Universitas Bina Sarana Informatika, 2019)
Abstract: Expert System is a knowledge-based program that offers quality solutions for problems within a certain domain. The implementation of expert systems is widely used for commercial purposes, because expert systems are seen as a way to store expert knowledge in certain areas in computer programs, so that they can make informed decisions and think intelligently. Using Android-based methods, this program is expected to represent experts in diagnosing Kip-Bangkok disease. Expert Systems Applications diagnosis chicken bangkok provide maximum convenience for the owner of the chickens Bangkok, so owners do not have chicken bangkok meet with specialists in person, the owner of the chicken bangkok open the computer and use this expert system application instead of the disease in poultry media consultation of experts in chickens bangkok. The expert system is used as a decision support and is used as a tool for someone who has no information about the types of diseases and symptoms in bangkok chicken, as well as preventative advice. From this problem this disease can be known on the basis of the symptoms found in chicken in Bangkok and to prevent deaths by giving appropriate prevention advice. Keywords: Expert system, Application, Diagnosis of the Chicken Disease of Bangkok